Random Attractors for Stochastic Retarded Lattice Dynamical Systems - Xiaoquan Ding; Jifa Jiang (Abstract and Applied Analysis)
This paper is devoted to a stochastic retarded lattice dynamical system with additive white noise. We extend the method of tail estimates to stochastic retarded lattice dynamical systems and prove the existence of a compact global random attractor within the set of tempered random bounded sets.